2005
DOI: 10.1139/x04-180
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of damage and mortality in red pine plantations following a major ice storm

Abstract: The impact of a major ice storm in eastern Ontario on 28 pine plantations (red pine, Pinus resinosa Ait.; Scots pine, Pinus sylvestris L.; white pine, Pinus strobus L.; and jack pine, Pinus banksiana Lamb.) was examined for 4 years after the event. Degree of crown loss and tree mortality were quantified in relation to tree and stand characteristics (e.g., tree species, diameter at breast height (DBH), stand density, stand edge versus interior). We also tested whether salvaging damaged material reduced subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Sites were selected in pairs across the study region (damaged and undamaged) with a minimum of 2 km between sites. In the damaged plantations, possible habitat for I. pini included snapped tops, standing snags, uprooted trees, blown-down trees and trees with varying degrees of crown loss (Table 1; Ryall & Smith, 2005).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sites were selected in pairs across the study region (damaged and undamaged) with a minimum of 2 km between sites. In the damaged plantations, possible habitat for I. pini included snapped tops, standing snags, uprooted trees, blown-down trees and trees with varying degrees of crown loss (Table 1; Ryall & Smith, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…In January 1998, a unusually severe ice storm throughout eastern United States and Canada caused extensive damage to numerous red pine, Pinus resinosa Ait., plantations across the region (Irland, 1998). The storm caused damage to red pine trees through up-rooting, blowing over, bending or completely breaking the stems (Ryall & Smith, 2005), creating a range of host material with varying levels of resistance to colonization by secondary bark and wood-boring beetles.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of predators and parasites also are associated with subcortical herbivorous insects (Dahlsten 1970;Ryall 2003). Thus, as the amounts and characteristics of CWD change over time (Ryall and Smith 2005;Wilson and McComb 2005), there will be changes and turnover of associated subcortical insect communities (Weiss 1920;Blackman and Stage 1924;Savely 1939;Wallace 1953).…”
Section: Introductionmentioning
confidence: 99%
“…Belanger et al (1996) found no difference in damage to loblolly pines of different size classes following an ice storm. Ryall & Smith (2005) observed that large diameter trees were less damaged by ice accumulation than small diameter trees. Therefore, it is necessary to consider more factors, such as tree species, age, development stage and health condition, when the role of tree size is assessed in determining its resistance to ice storms.…”
Section: Factors Affecting Ice Damage Severitymentioning
confidence: 96%
“…Ryall & Smith (2005) reported a strong positive relationship between crown damage and stand density for red pine (Pinus resinosa) plantations in Eastern Ontario, damaged by the 1998 ice storm. Cremer et al (1982) observed that overstocked or dense plantations suffered more severe damage than more widely spaced plantations with trees characterized by sturdier boles and well-developed canopies.…”
Section: Factors Affecting Ice Damage Severitymentioning
confidence: 99%